The mother tongue : The Story of the English Language - Bryson, Bill. (London : Penguin Books, 2009)
Covers the history of language from its beginnings to the explosion of English as a global language in the twentieth century.
Includes bibliographical references and index.
Adult.
Adult
Keywords: English language -- History; English language -- History